Regulating transnational heritage : memory, identity, and diversity - Bruncevic, Merima (New York, NY : Routledge, 2022)
"There is a vast body of international and national law that regulates cultural heritage. However, the current regulation remains quite blind to the so called "transnational heritage". This is heritage where there is no community recognized in law that it can be directly attributed to and that can be responsible for its safekeeping and preservation. It can also be items of heritage where the claim of ownership is disputed between two or more peoples or communities. Transnational heritage challenges the idea of monolithic, mono-cultural, ethno-national states. There are number of examples of such cultural heritage, for instance the Buddhist Bamiyan statutes in Afghanistan, Palmyra in Syria, the Jewish heritage of Iraq, or various items that are currently housed in large, often Western, museums, as a result of colonial practices. This book explores the regulation of transnational heritage. By discussing many cases of transnational heritage and the problems that arise due to the lack of regulation the book analyses the manifestations of memories and constructions of communities through heritage. It focuses particularly on the concept of community. How are communities constructed in cultural heritage law and what falls outside of the definitions of community? The book underlines that the issues surrounding transnational heritage involve more than a communal right to culture. It is argued that transnational heritage also directly affects wider matters of law such as citizenship, human rights, sovereignty, as well as the movement of people and cultural goods"--
Introduction -- Matter : current regulation and transnational heritage -- Movement : heritage without borders -- Diversity : transnational cultural heritage -- Constellations : the transnational in community -- Memories : new regulatory approaches.
Keywords: Cultural property -- Protection (International law); Cultural property -- Protection -- Law and legislation; LAW / General